Educational Model of Physical Training of Students of Bio-technological Profiles - Bogdan Semeniv; Andrew Babych; Petro Bilenjkyj; Taras Prystavsjkyj; Olexander Kovban (Lesya Ukrainka Volyn National University, 2018)
In modern socio-economic conditions professional training of students in higher educational institutions is of great importance, which most concretely represents the principle of organic connection of physical education with the practice of work. The assistance in the preparation of harmoniously, highly skilled specialists is the purpose of physical education in educational institutions. In the process of training from the course of physical education, the tasks are to be solved: education of students of high moral, volitional and physical qualities, readiness for highly productive work; preservation and strengthening of health, assistance in the correct formation and comprehensive development of the organism, support of high working capacity throughout the period of training; comprehensive physical training of students; their profile physical training taking into account the peculiarities of future labor activity; acquisition of students the necessary knowledge on the basics of theory, methodology and organization of physical education and sports training; education of students convinced of the need to regularly engage in physical education and sports. Ukraine has a wide range of activities that create the necessary working and living conditions, improve the external environment, including the production environment, the further development of health care. At the same time, human activity, physical culture and sports are important factors for improvement, health promotion, which ultimately enhances the creative activity of man and his ability to work. Physical culture is an integral part of human life. Physical exercises play a significant role in the ability of members of society, which is why knowledge and skills in physical culture should be laid out in educational institutions of different levels in stages. Despite the scientific achievements in the physical education and sport system, most of the issues of professional training were left out of the attention of domestic and foreign physicists and sports scientists. Taking into account this, we faced the task of developing an educational model of the professional physical training of students of the specialty of production and processing of livestock products and to identify the main components of the content of profiling physical training. We have developed the content of the curriculum for students of the specialization of the production and processing of livestock products, which consisted of two blocks: physical education and physical training.